Bis(μ-5-chloro-2-hydroxyacetophenone 4-nitro-benzoylhydrazonato)bis[dipyridinecadmium(II)] - Ali, Hapipah Mohd; Ng, S.W.; Aripin, N.F.K. (International Union of Crystallography, 2005)
The title dinuclear complex, [Cd2(C15H 10ClN3O4)2(C5H 5N)4], lies on a centre of inversion. The deprotonated Schiff base spans the meridional sites of the octahedron surrounding the Cd atom through its O, N and O atoms; the hydroxy O atom of the symmetry-related anion forms a square plane with these atoms, and the other two sites of the octahedron are occupied by the N atoms of the pyridine ligands. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.